Faktor Risiko Kelelahan Kerja pada Operator Internal Transfer Vehicle (ITV) di PT. Belawan New Container Terminal - Lubis, Fatma Sri Ramadhan; Arrazy, Syafran; Eliska, Eliska; Batubara, Abdul Karim (Fakultas Kedokteran Universitas Trisakti, 2025)
Background Occupational fatigue is an important issue in the field of occupational health and safety that is often experienced by workers in the industrial sector, especially workers who are involved in activities that are monotonous, repetitive, and last for a long duration of time. This condition can have an impact on reducing work productivity, increasing the risk of work accidents, and affecting the physical and mental health of workers. This study aims to analyze the risk factors associated with job fatigue in ITV (Internal Transfer Vehicle) Operators at PT Belawan New Container Terminal. Methods The research method uses a quantitative approach with a cross-sectional study design. The number of samples in this study were 39 respondents selected by total sampling technique. Data analysis was carried out through univariate analysis to describe the characteristics of respondents and bivariate analysis using the chi-square test to determine the relationship between independent variables, namely length of work, Body Mass Index (BMI), age, medical history, and work shifts with fatigue. Results The results showed a significant relationship between length of work (p = 0.005), BMI (p = 0.001), and work shift (p = 0.000) with job fatigue. However, the variables of age (p = 0.318) and medical history (p = 0.816) did not have a significant relationship. Therefore, the management is expected to formulate appropriate policies related to the setting of working hours. Conclusions The conclusion in this study is that there is a relationship between length of work, BMI, and work shifts with job fatigue, but there is no relationship between age and medical history. Therefore, management is expected to formulate appropriate policies related to setting working hours, structuring the shift system, and monitoring the nutritional status of workers in order to reduce the rate of fatigue.